A multifunctional fluorescent Cd-MOF probe: its synthesis, structure, and sensing properties. (14th April 2022) - Liu, Lu; Jia, Yuejiao; Chen,; Li, Dechao; Hu, Ming
Abstract : A Cd-MOF with a one-dimensional cavity can be used as a multifunctional fluorescent probe to effectively recognize CrO4 2− and Cr2 O7 2− ions, Fe 3+ ions and TNP molecules. Abstract : A 3D structure of Cd-MOF with a 1D cavity based on 4-(2, 2′:6′, 2′′'-terpyridine)-3, 5-benzenedicarboxylic acid ligand (H2 dbta) was obtained, namely, [Cd(dbta)] n (1 ). The size of the pore in complex 1 is 10.59 × 11.75 Å 2 . In addition, the surface area and pore size distribution of complex 1 were measured. The properties of the multifunctional fluorescent probe complex 1 were characterized in detail. Complex 1 can effectively identify CrO4 2− and Cr2 O7 2− ions, and also has high accuracy and recoverability for the identification of Fe 3+ ions and TNP molecules. The limits of detection for the tested substances were further determined. The sensing mechanisms of the fluorescent probe complex 1 for the above analytes were comprehensively explored.